Green biohydrogen production from renewable plant-based resources: A comparative evaluation - Goren, A. Yagmur; Dincer, Ibrahim; Khalvati, Ali (Process safety and environmental protection, 2024)
Increasing energy demand drives the need for environmentally sustainable and economically viable renewable resources to eliminate problems related to greenhouse gas emissions. In recent years, research on biohydrogen (bio-H2) production as a renewable energy source has been recognized as a potential subject. It aims to reduce the pressures set by carbon dioxide emissions and the depletion of fossil fuel supplies. The field of bio-H2 science is considered potentially important; there have been increasing efforts to develop feasible systems for viable applications. This review further presents an updated and comprehensive review of bio-H2 production by dark fermentation (DF), photofermentation (PF), microbial electrolysis cells (MEC), and hybrid processes using plant-based materials. Among these processes, the highest H2 production yield of 680.8 mLH2/g-biomass was obtained using the DF-PF hybrid process. A comparison of bio-H2 production yields, the environmental impact, and the costs of DF, PF, MEC, and hybrid systems is considered, and superior performance was obtained for integrated biological processes. The comparative evaluation results showed that the MEC process is the most economical technology, followed by integrated systems. The PF is the most environmentally friendly H2 production process, presenting the lowest global warming potential (GWP) value of 1.88 kgCO2eq./kgH2 and acidification potential (AP) of 3,61 gSO2/kgH2; it is followed by DF and MEC processes. On the other hand, the highest GWP of 14.8 kgCO2eq./kgH2 and AP 103 gSO2/kg H2 were obtained for the DF-MEC process related to electrical and heat requirements during the production process. Furthermore, the WCP and WSF values were 84.5 and 3632.9 m3 for the DF-MEC integrated process due to the water utilization in anode and cathode solutions, while WCP was 2.91 m3 for the DF process. Overall, the results of this study further revealed that substantial effort, in the current and future, should be performed on bio-H2 production from plant-based biomass using integrated biological processes. Moreover, the bibliometric analysis presented that bio-H2 production from plant-based materials, MEC systems utilization, and nano-additives are growing areas in the bio-H2 research that provide zero-carbon energy in the future.